Examination of Hepatitis B Exacerbation by Steroid Therapy for Patients with Acute Sensorineural Hearing Loss - Hirano, Kojiro; Kobayashi, Hitome; Tanaka, Yoshihito (The Journal of Japan Society for Infection and Aerosol in Otorhinolaryngology, 2019)
Acute sensorineural hearing loss is one of the frequently encountered diseases in otolaryngology, especially sudden deafness, which requires early intervention. There are a variety of treatments. The systemic administration of corticosteroids is currently common. However, corticosteroids have various side effects such as worsening of diabetes and elevation of blood pressure, and management is required for administration. The side effects also affect immunosuppression. The exacerbation of hepatitis B due to the administration of corticosteroid is described in immunosuppression/chemotherapy guidelines for hepatitis B countermeasures. We examined the presence or absence of the exacerbation of hepatitis B due to the treatment of hepatitis B positive cases in patients with acute sensory hearing loss who visited our hospital. The subject is an acute sensorineural hearing loss patient who presented at the Showa University Otolaryngology Department for 4 years from April 1, 2014, to March 31, 2018. Inoculation cases of hepatitis B virus vaccine were excluded. A total of 337 cases were included. Among them, 35 cases were positive for HBs antigen, HBs antibody, and HBc antibody. Regarding corticosteroid administration in any of the positive cases, PCR of serum HBV-DNA was carried out to confirm the amount of virus in the blood. There was no case detected at the initial inspection. There was no case where PCR was detected after one year. This was because the dose of corticosteroid used was not equal to or higher than the intermediate risk in the risk of the reactivation of hepatitis B. However, in this case, since there was no patient with detection sensitivity or higher in PCR originally and the number of cases per se was small, it is necessary to pay attention to the morbidity of HBV.